STUDENTS' PERCEPTION IN USING ZOOM APPLICATION DURING ONLINE LEARNING IN FKIP AT TRIDINANTI UNIVERSITY PALEMBANG - Fia Sisi Abriati; Yunani Atmanegara; Jenny Elvinna Manurung (Universitas Tridinanti Palembang, 2022)
The widespread use of the internet brings impact to education and provides the solution for many educational institutions to conduct online learning during Covid-19 pandemic.This study aimed to determine students’ perception in using Zoom application during online learning in Faculty of Teacher Training and Education at Tridinanti University Palembang. Descriptive quantitative survey method was carried out. This study involved 104 students who experienced online learning by using Zoom Application. For collecting the data, questionnaire was used and distributed online to the students. Most students perceived positively toward the use of Zoom application during online learning. The results of this study showed that: (1) Using Zoom application during online learning gave students new learning experience and benefits, (2) Zoom application offers some features that can be easily operated by the users, (3) Zoom application became online learning platform preference, (4) Using Zoom application could improve students ICT skill, (5) The use of Zoom application during online learning would be continuously used by students, and (6) Students did not find serious problem to participate in online learning using Zoom application. In brief, Zoom Application is an effective educational technology tool for online learning.Keywords:perception, online learning, Zoom application